A New Stress-reduction Model for Soil Arch in Landslides - Li, Xing-ming; Yan, E-chuan; Sun, Miao; Yao, Xian-wen; Li, Shuo; Gao, Cheng; Chen, Qian (Periodica Polytechnica Civil Engineering, 2023)
Stabilizing piles are extensively used as an effective landslide control treatment, and the soil arching effect is the key element for the performance of the pile system. Most previous studies on soil arching effect and its application in stabilizing piles were conducted with laboratory tests and numerical simulations, while limited efforts have been dedicated to the analytical characterization of such a soil-structure interaction. In this paper, a new stress-reduction model for soil arch in landslides is established by theoretical derivation. Our model calculation has demonstrated an exponential reduction in the stress along the direction of slipping between and behind stabilizing piles and thus justifies the observations of laboratory tests and numerical simulations. Thereafter, the analytical solutions to the two key arch shape parameters, namely the inclination angle at the foothold and the thickness of soil arch, are derived based on the proposed stress-reduction model. Then, the ultimate bearing capacity of soil arch between and behind stabilizing piles is subsequently calculated, and a three-level load sharing model for landslides is thus proposed based on the stress-reduction mode. The load sharing model can well capture the stage characteristics of the interaction between landslide mass and stabilizing piles. Finally, the calculation model of spacing between stabilizing piles is established based on the proposed stress-reduction model, and it turns to be good in field application. The findings of this study can contribute to a better understanding of the soil arching effect as well as a better design of the stabilizing piles.